Pelarangan Mutlak Khitan Perempuan Bertentangan Dengan Syariat: (Tinjauan Atas Fatwa MUI Perspektif Maqä€Á¹¢Id Al-Syaräª”˜ah) - Assalwa, Shafira Amalia; Ma'arif, Ilham Fikri (Faculty of Shariah UIN Ponorogo, 2024)
Talking about religious guidelines in Indonesia will not be separated from discussing the fatwa of the Indonesian Ulama Council (MUI). The religious fatwas produced by this organization often become references for Muslim communities in their daily lives. This article focuses on the MUI's fatwa on female circumcision, especially its statement that the absolute prohibition of female circumcision is contrary to Islamic law. According to MUI, female circumcision is part of the propagation of Islamic teachings. The research is studied through a qualitative approach using Jasser Auda's maqÄá¹£id al-sharÄ«'ah theory in formulating fatwas. The findings of this research reveal that many Muslim scholars and other authoritative fatwa institutions, both in Indonesia and the world, do not hesitate to prohibit female circumcision. Their opinion is not only based on medical advice that prohibits and states the absence of benefits from female circumcision but also based on and inspired by the purpose of Shari'ah, maqÄá¹£id al-syarÄ«'ah. This study reveals that MUI's claim that the absolute prohibition of female circumcision is not in line with the Sharia, carries consequences that are not light.